A novel concept of high temperature superconducting undulator. (21st September 2017) - Holubek, T; Casalbuoni, S; Gerstl, S; Glamann, N; Grau, A; Meuter, C; de Jauregui, D Saez; Nast, R; Goldacker, W
Abstract: The available variety of commercial high temperature superconducting (HTS) coated conductors resulted in the development of many different HTS based applications. One promising application to realize superconducting undulators for table top free electron lasers considers meander-structured stacked HTS tapes to provide the desired sinusoidal magnetic field pattern. One of the biggest challenges of this layout is to keep the resistance of the joints between the stacked tapes small. This paper presents a novel concept of a jointless undulator wound from a single HTS tape scribed with picoseconds laser pulses, preventing damage to the superconducting layer from overheating.